KONSUMSI KEDELAI DAN HASIL OLAHANNYA SEBAGAI SUMBER PHYTHOESTROGEN DAN KEJADIAN MENOPAUSE PADA IBU RUMAH TANGGA DI KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Wagustina, Silvia; Zulfah, Siti; Afdayani, Nova (Lembaga Penerbitan Unversitas Esa Unggul, 2018)
Women age epectancy is more higher than men, and it will be more elderly women than men among elderly population as the consequency. The long term impact there will be some health problem such as; osteoporosis, coronary heart desease, stroke, diabetes mellitus, senile, alzheimer, etc. One of the way to surpress the menopause simptoms is increase the intake of soy bean and its product due to the isoflavon in it. which similar part with estrogen. The aim of this study was to figure out the impact of concumption habit of soy bean and its product to the menopause level among housewifes. This research was the descriptive analitic reasearch, designed with case control study, to figure out the impact of consumption habit of soy bean and its product to the early menopause. The samples were inclusive criteria of housewives. The analysis tools which used were Chi square test and odds ratio. Result of this study showed that consumption habit of soy bean and its product were enough in case group 47,7% and in controlled group 79,5%. Menopause periode in group caseaverage early (40-50 year) 45,5%. There was meaningful impact from the consumption habit of soy bean and its product in menopause periode (age) (p < 0,05) with OR = 0,235. As the conclusion, itâ€™s known that enough Soy bean and its product consumption could be a protective factor against early menopause. It is suggested for women to comsume high isoflavon food source about â‰¥ 30 mg/day to prevent early menopause.Â Keyword : Isoflavon intake, soybean, fitoestrogen, and menopause